2016
DOI: 10.1016/j.jcma.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea and risk of aortic dissection: A nonrandomized, pair-matched cohort study

Abstract: SA was not associated with an increased risk of AD using a large nationwide cohort database. Nonetheless, larger prospective studies or meta-analyses are recommended to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In this regard, a recent case control study utilizing a large national health insurance database of about 50,000 people in Taiwan is of interest. This study, however, found no association between the diagnosis of OSA and future incidence of aortic dissection [33]. However, bias may be present as individuals with undiagnosed OSA would have been misclassified as not having OSA.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, a recent case control study utilizing a large national health insurance database of about 50,000 people in Taiwan is of interest. This study, however, found no association between the diagnosis of OSA and future incidence of aortic dissection [33]. However, bias may be present as individuals with undiagnosed OSA would have been misclassified as not having OSA.…”
Section: Discussionmentioning
confidence: 89%
“…Totally three publications were identified for this analysis including one cohort and two case-controls. 16,21,24 Data pooled showed an association between OSA (AHI ! 5) and AD (Figure 2, OR 1.60; 95% CI 1.01-2.53; p ¼ 0.04), though two of them showed no significance within the comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Finally seven publications containing one cohort study, four case-controls, and two cross-sectional researches, with total 56,291 participants were analyzed in this study. 16,[21][22][23][24][25][26] The researches were all single center and six of them were from Asia. The only cohort study which included the most population was conducted in Taiwan.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that patients with aortic diseases such as AA have a high incidence of moderate-to-severe OSA [17]. By contrast, another study including an Asian population revealed that OSA was not associated with an increased risk of aortic dissection [31]. Age, male sex, hyperlipidaemia, hypertension, obesity, and tobacco use are well-known risk factors for AA [32].…”
Section: Discussionmentioning
confidence: 99%